PENGARUH ASIMETRI INFORMASI TERHADAP PRAKTIK MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI BEI - SANTOSO, YOUNGKIE (: 2303-1719)
Theory of Agency which implication of asimetri information arising from the existence of difference of importance between manager with stockholder. Where manager have more information to arrange accountancy numbers specially profit undetected by stockholder. Arrangement of that accountancy often referred as earning management. This research aim to to find empirical evidence of influence of information asimetri to earning management with variable control operation cash flow varians ( CFVAR), growth of company ( GROWTH), company size measure ( SIZE), and mean of kapitalisasi market ( MKTBV). Desain Research used is research with hypothesis. Tied variable and free variable in this research is earning management which to proxy in accruals discretionary and of asimetri information which to proxy with spread bid-ask relative. Sampling in this research is manufacturing businesss which enlist in Effect Exchange Indonesian start year 2006-2010 counted 67 company. Data analysis which used in this research cover classic assumption test that is test of normality, test multikolinearity, test autocorelation, and test of heterokedastisition. Later, then examination of hypothesis with analysis of regretion doubled. Result of examination by simultan indicate that information asimetri and variable control operation cash flow varians, growth of company, company size measure, and mean of capitalitation market have an effect on by significate to earning management. This indicate that information asimetri and all control variable can explain earning management. Besides, variable control operation cash flow, growth of company, and mean of kapitalisasi market don’t have an effect on to earning management, only company size measure having an effect on by significate to earning management.